Visual symbolism of Malay nationalism towards Malay unity / Khairudin Murad - Murad, Khairudin (2020)
The formulation of this research is greatly influenced by visual symbolism to uplift Malay nationalism life-giving principle. Although there are several past researches focusing on Malay nationalism in regards with politics, economy, arts and socio-culture, the relationship between visual communication and symbolism towards nationalism as triggering factor is yet to be scrutinized profoundly. This research is aim to measure the influence of moderator variables (demographics variables) and mediator variables. The moderator and mediator are significant factors on the relationship between independent and dependent variables. The three independent variables in this study are visual symbolism awareness, Malay nationalism awareness and visual symbolism of Malay nationalism. The variable conceptual and operational definition is proposed based on the theories guiding the study and related previous studies. The importance of conceptual and operational in this study is to highlight and determine the precise definition enclosed by the measured characteristic. The accuracy of variables’ operational definition leads to preferable research outlines that are measured by moderation, mediation, independent and dependent variables. There are 18 hypotheses developed in this study and all hypoptheses is accepted due to its significance. Quantitative research is employed to gather data collection from the study. Analytical survey is applied to validate the measurement from the sample of population. This research method and data collection is desired among visual and nationalism researchers where SPSS statistical software was utilized for preliminary data processing and AMOS was employed for multivariate statistical data processing. In order for 450 respondents designate the representative of population, appropriate statistical techniques need to be generalized. Moreover, the aim of this study is to identify the patterns, strengths and directions of the relationship among the variables. The analysis on mediationalmoderated of VSMNU path model reveals that all moderator variables are significantly positive in VSMNU nested path model. However, analyses on individual path parameters reveal that certain moderator variables have affected some path parameters. Therefore, all hypothesized measurement models employed in this study, namely VSA, MNA, SIMN, VSMN, NLA and MUPB is confirmed. The findings of this study can contribute to the enhancement of the knowledge in the fields, and provide valuable information to stake holders such as media and communication industries, policy makers as well as the academician who have interest in the subject areas. All of these parties can employ or manipulate these mediator variables in order to minimize the negative exposure or to maximize the positive exposure to visual symbolism through Malay nationalism unity awareness.